2023
DOI: 10.1021/acs.jafc.3c01169
|View full text |Cite
|
Sign up to set email alerts
|

Upcycling of Soy Whey with Ischnoderma benzoinum toward Production of Bioflavors and Mycoprotein

Abstract: Soy whey is becoming a worldwide issue as a liquid waste stream that is often discarded after tofu, soy protein, and soy-based dairy alternative manufacturing. This study established a model to produce a bioflavor and mycoprotein using fermentation of soy whey by a basidiomycete Ischnoderma benzoinum. Under the dedicated control of a fermentation system, an intense almond-like and sweetish aroma was perceived by a trained sensory panel (n = 10) after fermentation of pure soy whey within 20 h. By application of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…4-Methoxybenzaldehyde has been detected in the broth of edible mushroom by liquid fermentation using Ischnoderma resinosum, and it has been considered as a key odorant for the fermentation product, and the formation pathway of 4-methoxybenzaldehyde has been verified by via isotope tracer method. , Research has shown that the content of 4-methoxybenzaldehyde increased significantly during fermentation of bioflavors and mycoprotein by Ischnoderma benzoinum . Thus, we speculate that 4-methoxybenzaldehyde may be the metabolite from fungal fermentation.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…4-Methoxybenzaldehyde has been detected in the broth of edible mushroom by liquid fermentation using Ischnoderma resinosum, and it has been considered as a key odorant for the fermentation product, and the formation pathway of 4-methoxybenzaldehyde has been verified by via isotope tracer method. , Research has shown that the content of 4-methoxybenzaldehyde increased significantly during fermentation of bioflavors and mycoprotein by Ischnoderma benzoinum . Thus, we speculate that 4-methoxybenzaldehyde may be the metabolite from fungal fermentation.…”
Section: Resultsmentioning
confidence: 81%
“…25,26 Research has shown that the content of 4methoxybenzaldehyde increased significantly during fermentation of bioflavors and mycoprotein by Ischnoderma benzoinum. 31 Thus, we speculate that 4-methoxybenzaldehyde may be the metabolite from fungal fermentation. In fact, a variety of benzaldehyde derivatives including 4-methoxybenzaldehyde can be produced by fermentation via E. cristatum, and they show an anti-inflammatory activity.…”
Section: ■ Materials and Methodsmentioning
confidence: 87%
See 1 more Smart Citation
“…Concurrently, I. benzoinum biomass accumulated, which contained 73.2 mg/g of crude protein. 2 Coffee is a popular beverage around the world. The postharvest treatment of coffee beans is of great importance for the quality from a sensory point of view.…”
Section: Conference Sessionsmentioning
confidence: 99%
“…Under the optimized fermentation conditions, an intense almond-like and sweetish aroma, shaped especially by benzaldehyde and 4-methoxybenzaldehyde (anisaldehyde), was produced in submerged cultures of the fungus. Concurrently, I. benzoinum biomass accumulated, which contained 73.2 mg/g of crude protein …”
Section: Selected Contributions From the Specific Conference Sessionsmentioning
confidence: 99%